Precipitable Water Vapour and Zenith Total Delay time series and models over Slovakia and vicinity - IGONDOVÁ, Miroslava; CIBULKA, Dušan (Contributions to Geophysics and Geodesy, 2010)
More than 50 permanent GNSS (Global Navigation Satellite Systems) stations are processed continually within the Central European Permanent Network. Zenith Total Delay (ZTD), one of the processing outputs, reflects a delay of the GNSS signal caused by troposphere. Precipitable Water Vapour (PWV ) is calculated when ground meteorological observations are available. Model of PWV over Slovakia and its vicinity is produced using digital elevation model data for height correction. Real variation of PWV over the area shows a model of normalized PWV (nPWV ), which is created from PWV values reduced by theoretical PWV values corresponding to altitude and latitude of the station. Time series of ZTD and PWV since 1996 and models of PWV and nPWV are published on the web page, using Web Map Service and other web technologies. Data are continually updated and can be downloaded for free.